The concessionaire's dilemma - Mohd Ishan, Zahira; Ab Rahman, Rozanah (Universiti Putra Malaysia Press, 2011)
This case is about the problem faced by Tempias Cahya Sdn Bhd (Tempias) in deciding whether there was a valid agreement between it and Sejahtera Marina Resort Bhd (SMRB). This problem arises when a draft formal agreement by SMRB contained several new conditions which were never previously raised nor agreed upon by Tempias. When Tempias requested for further time to study the draft formal agreement, SMRB responded that they would not be signing the formal agreement between them and gave notice to Tempias to vacate SMRB’s premise. If there were already a valid agreement between the parties, Tempias would not need to vacate the premise and can claim all monies due to them. On the other hand, if there were no valid agreement in place, Tempias would lose an amount close to RM1m. This study illustrates how extrinsic evidences would be used to determine the existence of a contract and the importance of offer and acceptance as elements of contract.